Challenging the concept of electrochemical discharge using salt solutions for lithium-ion batteries recycling. (June 2018) - Ojanen, Severi; Lundström, Mari; Santasalo-Aarnio, Annukka; Serna-Guerrero, Rodrigo
Graphical abstract: Highlights: Critical evaluation of Li-ion Battery discharge in brine solutions. LIB can be discharge in NaCl within our depending on salt concentration. Addition of mixing in the solution can prevent precipitate formation. Presence of metal particles significantly enhances the discharge reaction. Direct submerging batteries into brine solution resulted as connector corrosion. Abstract: The use of lithium-ion batteries (LIB) has grown significantly in recent years, making them a promising source of secondary raw materials due to their rich composition of valuable materials such as Co, Ni and Al. However, the high voltage and reactive components of LIBs pose safety hazards during crushing stages in recycling processes, and during storage and transportation. Electrochemical discharge by immersion of spent batteries in salt solutions has been generally accepted as a robust and straightforward discharging step to address these potential hazards. Nonetheless, there is no clear evidence in the literature to support the use of electrochemical discharge in real systems, neither are there clear indications of the real-world limitations of this practice. To that aim, this work presents a series of experiments systematically conducted to study the behavior of LIBs during electrochemical discharge in salt solutions. In the first part of this study, a LIB sample was discharged ex-situ using Pt wires connected to the battery poles and submerged into the electrolyte solution on the opposite end. The evolution of voltage in the battery was measured for solutions of NaCl, NaSO4, FeSO4, and ZnSO4 . The results indicate that, among the electrolytes used in the present study, NaCl solution is the most effective for LIBs discharge. The discharge of LIB using sulfate salts is however only possible with the aid of stirring, as deposition of solid precipitated on the electrodes hinder the electrochemical discharge. Furthermore, it was found that the addition of particulates of Fe or Zn as sacrificial metal further enhances the discharging rate, likely due to an increased contact area with the electrolyte solution. While these findings support the idea of using electrochemical discharge as a pre-treatment of LIBs, severe corrosion of the battery poles was observed upon direct immersion of batteries into electrolyte solutions. Prevention of such corrosion requires further research efforts, perhaps focused on a new design-for-recycling approach of LIBs.